2021
DOI: 10.1177/2040620721989586
|View full text |Cite
|
Sign up to set email alerts
|

Current and novel BTK inhibitors in Waldenström’s macroglobulinemia

Abstract: The current therapeutic approach in Waldenström’s macroglobulinemia (WM) is being driven by insights in disease biology and genomic landscape. Bruton’s tyrosine kinase (BTK) plays a key role in signaling pathways for the survival of WM clone. BTK inhibition has changed the treatment landscape of the disease. Ibrutinib has resulted in deep and durable responses both as an upfront and salvage treatment with a manageable toxicity profile. However, the need for fewer off-target effects and deeper responses has res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 125 publications
0
11
0
Order By: Relevance
“…[99][100][101][102] In one study, 2-year event-free survival (measured from the time of treatment initiation to disease progression, treatment toxicity or death from any cause) was 80%. 92 Although secondgeneration BTKi have shown promise in treating systemic LPL, 103 we found no reported data on these agents in the context of BNS.…”
Section: Bing-neel Syndromementioning
confidence: 85%
“…[99][100][101][102] In one study, 2-year event-free survival (measured from the time of treatment initiation to disease progression, treatment toxicity or death from any cause) was 80%. 92 Although secondgeneration BTKi have shown promise in treating systemic LPL, 103 we found no reported data on these agents in the context of BNS.…”
Section: Bing-neel Syndromementioning
confidence: 85%
“…Ibrutinib is often accompanied by AEs including atrial fibrillation, bleeding events, and hypertension, leading to discontinuation of the treatment in 5%–10% of patients with WM 5,7–9 . Systematic reviews of ibrutinib studies using eight randomized controlled trials for B‐cell malignancies revealed a relative risk for atrial fibrillation and hypertension of 4.69 and 2.82, whereas patients suffering life‐threatening arrhythmias have also been reported 27–29 . In the ASPEN clinical trial, patients receiving zanubrutinib had a lower incidence of atrial fibrillation, bleeding AEs, and hypertension compared with those taking ibrutinib, leading to lower treatment discontinuation rate in patients on zanubrutinib treatment 20 …”
Section: Discussionmentioning
confidence: 99%
“… 5 , 7 , 8 , 9 Systematic reviews of ibrutinib studies using eight randomized controlled trials for B‐cell malignancies revealed a relative risk for atrial fibrillation and hypertension of 4.69 and 2.82, whereas patients suffering life‐threatening arrhythmias have also been reported. 27 , 28 , 29 In the ASPEN clinical trial, patients receiving zanubrutinib had a lower incidence of atrial fibrillation, bleeding AEs, and hypertension compared with those taking ibrutinib, leading to lower treatment discontinuation rate in patients on zanubrutinib treatment. 20 These results supported the idea that the second‐generation BTK inhibitor could minimize off‐target effects such as HER2 and TEC kinases and reduce toxicities related to BTK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that it is reasonable to switch to another regimen in the case of nonresponse or relapse. Second-generation BTK inhibitors have demonstrated safety and efficacy for WM patients [ 13 - 14 ] and may prove useful in treating BNS as well. Finally, autologous stem cell transplant has achieved remarkable results in a small case series, where 11/14 patients with BNS showed disease response and 10/14 remained in remission at three years [ 15 ].…”
Section: Discussionmentioning
confidence: 99%